Análise relacional intrainstitucional: redes de coautoria e acoplamento de autores - Franco, Nathalia Mendes Gerotti (2018)
Research on the impacts of collaboration on scientific works has been growing in recent years, mainly focused on a look at the political implications and allocation of financial resources. Scientific collaboration can encompass various levels of analysis, with emphasis on the internal - intrainstitutional, (intra) national - or situating what is being analyzed in an external context - interinstitutional, international and others. However, the issue of intra-institutional collaboration and identification of collaboration opportunities has little approach and studies. There is no knowledge of studies that deal with these two themes simultaneously in order to identify opportunities for collaboration within an institution. Thus, this paper presents an overview of the scientific collaboration between the professors of a federal university in the state of São Paulo, and presents a procedure to identify potential researchers for future collaborations. The identification of these potential collaborations is based on the coupling of authors by subject matter through the keywords that the teachers themselves put into their Lattes Curricula. In Brazil, the Lattes Curriculum is a platform that brings together a vast set of data on the performance of Brazilian researchers, which includes their main activities and academic achievements. For this work, data were extracted from the Lattes Platform using the SyncLattes tool developed by the NIT / Materials research group, and the processing of these data was done through Vantage Point software. Besides the elaborations of the matrices and networks, made with the software UCINET / NetDraw and Gephi. To identify the university's collaborative profile, a data sample containing 27,107 publications with 1,576 teachers was used. And for the analysis of the potential collaborations, a second data sample was used with 755 publications, 478 teachers and 1,717 key words. As a result, a set of indicators is presented on the scientific collaboration within the institution that is the focus of the study, as well as a keyword affiliation network, where it is possible to identify researchers with high potential for collaboration, which may help the teachers themselves to locate its potential partners, but it can also be used by strategic institutional bodies to foster collaboration among internal teachers to the organization. Based on the theoretical review and the analysis of the results it is concluded that there is a great collaborative potential still little explored.